Mewujudkan Sistem Pengelolaan Sampah Melalui Program Citarum Harum - Zakia Zakia; Dwi Agustina; Maya Puspita Dewi; Mary Ismowati; Resista Vikaliana; Munir Saputra (Institut Ilmu Sosial dan Manajemen Stiami, 2019)
As the most important component in life, the existence of water should be preserved and preserved. The principles of water conservation must be adhered to in daily life so that water sustainability can last into the future. The Citarum River as one of the biggest water potentials in West Java has a huge potential for the community, both for its beneficial potential and for its detrimental potential. Unfortunately, the community and the government tend to be lulled by the beneficial potential of the Citarum river, and unwittingly increase the potential loss of the river. Reduced land conservation areas, densely populated settlements, pollution of rivers by domestic and industrial waste, and others cause disasters such as floods, droughts and landslides. This is a problem that must be resolved together between the government and the community. Coordination, division of responsibilities, and harmonious communication between the two are believed to solve the complicated problems that occur in the Citarum River Basin.